Conducting a Grounded Theory Study in the Wake of a Traumatic Event: A Research Protocol - Adele Ferguson; Kim Ward; Rachael Parke (International Journal of Qualitative Methods)
Aims To explore the perspectives of people who worked at Whakatāne Hospital during and following a mass casualty event from the Whakaari/White Island eruption in New Zealand. Background The eruption of Whakaari / White Island on December 09th, 2019, significantly impacted many people in New Zealand and internationally. Whakatāne Hospital, a rural hospital in New Zealand, received a mass casualty alert in response to this event. Whakaari holds genealogical significance for Māori (Indigenous) people of the Mataatua region, the Eastern Bay of Plenty. Many local stories and waiata (songs) about this ancestral volcano are still told today. Design A research protocol for conducting a grounded theory study in the wake of a traumatic event. Methods Grounded theory (GT), a structured yet flexible methodology, is ideal for understanding a phenomenon in a research area where evidence is limited. It asserts that reality is constructed by those who experience it. In this context, recognising cultural knowledge ( Mātauranga Māori) is crucial to ensure the validity of cultural inclusivity and equity in the research process and generation of data. Conclusion The GT developed from this study will be based on the experiences of selected participants and will also explore the importance of cultural factors, such as indigenous knowledge, in conducting research on traumatic events. Implications for the Profession and for Patient Care The results from this grounded theory research will provide data for healthcare practitioners in developing resources and policies to enhance health system preparedness and responsiveness to disasters, improving future crisis management protocols. Reporting Method EQUATOR guidelines have been adhered to Consolidated criteria for reporting qualitative research COREQ. Public Contribution Mr Arona Smith and Mrs TeReinga.Kingi-Chase were actively involved in the design of this study, contributing their expertise in Mātauranga Māori.